Niepewność i ryzyko na elastycznym rynku pracy - Fiedor, Bogusław; Matysiak, Andrzej (Uncertainty and Risk in Perfectly Flexible Labor Market, 2006)
The paper starts with some introductory considerations on how different schools in contemporary economic theory consider the linkages between rigidity and - on the other hand - liberalization of the labor market and employment and unemployment tendencies. Against this background, the authors raise the hypothesis that the elastic or deregulated labor market may bring about some socially undesirable outcomes, concerning the family and child upbringing. First and foremost, elastic labor market increases risk and uncertainty faced by employees. This risk, is however, very much diversified with respect to two large groups this market is consisted of: knowledge providers and work providers. According to the authors, main criterion of that discrimination on the labor market is the human capital value. Following the above formulated categorization, they try to illuminate the linkages between the knowledge sector and contemporary work (as a production factor). In subsequent part of the paper, the authors systemize dangers and benefits resulting from elastic labor market to both employers and employees. They also point out factors which determine the efficiency of elastic labor market in addressing the unemployment problem using - for the sake of illustration - the case of German Mini Jobs. The final part of the paper highlights the issue whether and to what extent the elastic labor market, being characterized by increased work mobility and availability, may result in growing social imbalance and in posing serious threats to the very existence of the family.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1138, s. 114-124